2021
DOI: 10.1136/jitc-2021-003354
|View full text |Cite
|
Sign up to set email alerts
|

4-1BB and optimized CD28 co-stimulation enhances function of human mono-specific and bi-specific third-generation CAR T cells

Abstract: BackgroundCo-stimulatory signals regulate the expansion, persistence, and function of chimeric antigen receptor (CAR) T cells. Most studies have focused on the co-stimulatory domains CD28 or 4-1BB. CAR T cell persistence is enhanced by 4-1BB co-stimulation leading to nuclear factor kappa B (NF-κB) signaling, while resistance to exhaustion is enhanced by mutations of the CD28 co-stimulatory domain.MethodsWe hypothesized that a third-generation CAR containing 4-1BB and CD28 with only PYAP signaling motif (mut06)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 49 publications
(69 reference statements)
0
46
0
Order By: Relevance
“…The superior cytotoxic activity of M28z CAR T cells following antigen exposure, is in concordance with the elevated effector functions associated with the TemRA phenotype. Previous reports have demonstrated skewness toward the effector phenotype in CD28-containing CAR T cells and central memory phenotype in 4–1BB containing CAR T cells 19 , 36 , 37 although this finding has not been universal. 38 …”
Section: Discussionmentioning
confidence: 82%
“…The superior cytotoxic activity of M28z CAR T cells following antigen exposure, is in concordance with the elevated effector functions associated with the TemRA phenotype. Previous reports have demonstrated skewness toward the effector phenotype in CD28-containing CAR T cells and central memory phenotype in 4–1BB containing CAR T cells 19 , 36 , 37 although this finding has not been universal. 38 …”
Section: Discussionmentioning
confidence: 82%
“…However, it has been demonstrated that 4-1BB co-stimulation could ameliorate CAR-T cell exhaustion compared with CD28 co-stimulation (191,192). Remarkably, combining CD28 and 4-1BB could simultaneously augment the anti-tumor effects and increase the persistence of CAR-T cells (193)(194)(195)(196). In addition, the CAR-T cell structure can be optimized by the fully humanized CARs.…”
Section: Regulating the Persistence Of Car-t Cellsmentioning
confidence: 99%
“…Due to the success of CD28 and 4-1BB containing second generation CAR-T cells, current research efforts are exploring attributes of additional co-stimulatory domains—including ICOS (CD278), OX40 (CD134) and CD27—or the combination of multiple co-stimulatory domains, as in the case of third generation CAR-T cells [ 59 , 60 , 61 , 62 , 63 ]. Third generation CAR-T cell products incorporate two co-stimulatory domains within the cytoplasmic signaling tail with the attempt of providing added benefits and overcoming limitations of any one co-stimulatory signal [ 64 ].…”
Section: Structure and Design Of The Chimeric Antigen Receptor (Car)mentioning
confidence: 99%
“…The choice of co-stimulatory domain included in the CAR can greatly impact several key aspects of CAR-T cell therapy such as the differentiation state of the infusion product, the kinetics of anti-tumor response, cytotoxic function and associated toxicities. Recent work has proposed that an optimized co-stimulatory signal can generate a more desirable CAR-T cell product with an extended in vivo life span [ 59 ]. This notion stems from prior evidence showing that excessive co-stimulation is detrimental to CAR-T cell performance [ 71 , 72 ], and that mutation of specific residues within the cytoplasmic tail of a CAR that disrupt downstream signaling enhanced anti-tumor efficacy and CAR-T persistence in vivo [ 60 , 73 , 74 ].…”
Section: Structure and Design Of The Chimeric Antigen Receptor (Car)mentioning
confidence: 99%